Complex surgical treatment of congenital tracheal stenosis with associated unilateral lung agenesis - Akinori Sekioka; Koji Fukumoto; Masaya Murata; Ryohei Fukuba; Masaya Yamoto; Toshiaki Takahashi; Kei Ohyama; Akiyoshi Nomura; Yutaka Yamada; Naoto Urushihara (Elsevier, 2018)
Background: The combination of congenital tracheal stenosis (CTS) and unilateral pulmonary agenesis is rare and fatal. Especially, right lung agenesis is associated with dextrocardia and often causes tracheal alignment disorder. The mortality is estimated with 12.5-65%. Slide Tracheoplasty (ST) has been improved the prognosis, however, the postoperative course of CTS with single lung remains unclear. Here, we describe the postoperative challenging situation with bronchial intervention and other devices. Case presentation: A 9-month-old girl with CTS, right lung agenesis, dextrocardia, and bilateral superior vena cava underwent ST anterior to the aortic arch. On postoperative day 50, tracheostomy was performed for long-term airway pressure support. Six months after the ST, she showed severe bronchomalacia at the bifurcation of the lobar bronchi, which was sandwiched between the descending aorta and left pulmonary artery. Direct bronchopexy and mobilization of left pulmonary artery resolved the severe bronchomalacia. Additionally, the kinked trachea caused a tracheal ulcer and frequent accidental decannulations. The ulcer was made above the aortic arch by contact with the tracheal cannula. The customized Montgomery T-tube solved both problems and enabled the stable management for airway. Her condition eventually improved, and she was discharged home after 14 months of hospitalization. Conclusion: This case presented a very rare and critical condition. This is the first report to address the severe condition after ST anterior to the aortic arch. Surgical interventions or other devices for treatment are thought to be modified according to each condition. Keywords: Conjenital tracheal stenosis, Unilateral pulmonary agenesis, Dextorcardia, Bronchomalacia, Direct bronchopexy, Customized Montgomery T-tube